ANALISIS CEMARAN RESIDU LOGAM BERAT DAN RESIDU PESTISIDA ORGANOFOSFAT PADA DAGING, HATI DAN GINJAL SAPI - Bambang Kuntoro; Rarah Ratih Adjie Maheswari; Henny Nuraini (State Islamic University of Sultan Syarif Kasim Riau, 2012)
Meat is one of the most important foods to meet the needs of the human protein. Therefore, the meat should be safe and healthy for consumption and free of contaminants that can cause illnesses such as the contamination of heavy metals residues and pesticide residues. This study aims to determine the residual content of heavy metals (Pb, Cd and Hg) and organophosphate (OP) pesticide residues on the meat, liver and kidney. Random sampling was done on a population of livestock owners that slaughtered atSlaughterhouse Pekanbaru city. For evaluation, five livestock owners were sampling randomly to analysis. Sample used for analysis were the meat samples of bicep femoris (BF), liver and kidney. The variables observed in this study were the residues heavy metals (Pb, Cd and Hg) and organophosphate (OP) pesticide residues. Results showed that heavy metal contamination of residues in meat, liver and kidney beef were under the maximum allowed according to SNI. The respective heavy metal contamination was Pb (0,00-0,92 ppm), Cd (0,00-0,60 ppm) and Hg (0,00-0,03 ppm), while the organophosphate pesticide residues were less than 0005 ppm or below the maximum limit set by Indonesian National Standard (ISN) 7313: 2008 on limit maximum pesticide residues in agricultural products. In conclusion, the meat, liver and kidneys of cattle distributed traditionally at the market in Pekanbaru city had contamination levels of heavy metals (Pb, Cd and Hg) and pesticide residues organophosphate which were under maximum conditions specified